Adrenal Hemorrhage in the Deceased Neonate Referred to Tehran Legal Medicine Organization - Najari, Fares; Emam Hadi, Mohammad Ali; Khalilzadeh, Marzieh; Soleimani, Leila; Najari, Dorsa (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Adrenal hemorrhage during neonatal phase is more prevalent than was thought before and most of the cases are diagnosed after the autopsy. However massive hemorrhage is rare. The mozst important cause of adrenal hemorrhage is perinatal injuries, but large fetal size, maternal diabetes, congenital syphilis, anoxia, hemorrhagic diseases and immaturity are predisposing factors. Incidence rate of adrenal hemorrhage is 0.2% to 0.5% during perinatal phase. The diagnosis of the adrenal hemorrhage in this phase is rare. Our case was a four-day-old full term neonate who was born via normal vaginal delivery, with Apgar score 3. The baby was intubated immediately which was followed by seizure attacks and unfortunately death on the fourth day of life. The neonate was female with 3100 g weight. At autopsy the left kidney appeared larger than normal and the adrenal subcapsular hematoma which amounts to about 50 mL, was seen. According to previous studies delivery per vaginam, macrosomia and acidemia are some important risk factors for adrenal hemorrhage. Risk factors of the present case were normal vaginal delivery and acidemia. The neonate may present no symptom or sign during fetal or neonatal phase. So serial sonography is considered one of diagnostic methods.